Taxing democracy : local taxation and the social contract in America - Manning, Carrie (Book collections on Project MUSE., 2023)
Carrie Manning's illuminating book examines how policies to limit taxation at state and local levels in the US have direct and lasting consequences for equity, accountability, and ultimately for democracy.